WAYS OF INCREASE OF OPERATIONAL EFFICIENCY OF CRUCIBLELESS FURNACES OF REFLECTING TYPE FOR MELTING, STORAGE AND MELT DISCHARGE - A. T. Volochko; P. S. Grinchuk; G. V. Markov; A. A. Zhukova (Литьë и металлургия, 2011)
The brief information about crucibleless furnaces of reflecting type of melting, storage and melt discharge is given. For the purpose of increase of their effectiveness the theoretical calculation on optimization of multilayer brickwork parameters is carried out as well as composition of lining material is chosen.